PENGUATAN KAPASITAS MASYARAKAT DALAM MENINGKATKAN IMUNITAS SELAMA PANDEMI COVID-19 - Bambang Aditya Nugraha; Sulastini; Sandra Pebrianti (Jurnal Pengabdian Masyarakat DEDIKASI, 2022)
Covid-19 is a disease caused by a corona virus that was first discovered in the province of Wuhan, the People's Republic of China and has become a global pandemic. The virus attacks the respiratory system and causes mild disturbances to death. The severity of the symptoms that appear is related to the state of immunity. The worse the immunity, the more susceptible to contracting Covid-19. In addition, individuals with poor immunity tend to experience severe manifestations of covid. Therefore, it is important to increase immunity during the Covid-19 pandemic. Efforts made to increase immunity include increasing community capacity through community service activities in the form of a webinar entitled "Tips to Increase Immunity During a Pandemic". There is a difference in the average value of the pre-test (83.79) and post-test (96.21) after the activity. As many as 66.7% of participants considered that the activity went very well. Thus, the webinar that was held was useful in increasing community capacity in increasing immunity during the co-19 pandemic. It is hoped that this activity will continue to be carried out at different targets in order to reduce the spread and transmission of Covid-19.